Measurement in Machining and Tribology - Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the research advances in the science of measurement, giving special focus to the field of machining and tribology. Topics such as dimensional metrology, precision measurements, industrial metrology, accuracy and precision in measurement are covered. Also theoretical aspects such as modelling and simulation are highlighted.
Importance of temperature in metal cutting and its proper measurement/modeling -- The role of oxygen in orthogonal machining of metals -- Geometric accuracy of machine tools -- Machine vision in measurement -- Tribological Measurement of Electroless Nickel Coatings.
Keywords: Industrial engineering; Production engineering; Measurement; Measuring instruments; Materials -- Analysis; Coatings; Tribology; Corrosion and anti-corrosives.; Industrial and Production Engineering; Measurement Science and Instrumentation; Characterization and Analytical Technique; Coatings; Tribology; Corrosion